2012
DOI: 10.1530/rep-11-0302
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal hormone changes and growth in lambs born to dams receiving differing nutritional intakes and selenium supplementation during gestation

Abstract: To investigate the effects of maternal selenium (Se) supplementation and nutritional intake during gestation on hormone changes, percentage body weight (BW) change, and organ mass in neonatal lambs, ewes were allocated to differing Se levels (adequate Se (ASe, 11.5 mg/kg BW) or high Se (HSe, 77.0 mg/kg BW)) initiated at breeding and nutritional intake (60% (RES), 100% (CON), or 140% (HIGH) of NRC requirements) initiated at day 40 of gestation. At parturition, all lambs were removed from dams, fed common diets,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
(43 reference statements)
2
8
0
Order By: Relevance
“…In addition to observed differences in lactational performance of ewes, lamb growth, health, body composition, and endocrine status were altered by gestational nutrition in this study (Meyer et al, 2010b;Camacho et al, 2011;C. J.…”
Section: Potential Impacts Of Milk Productionmentioning
confidence: 55%
“…In addition to observed differences in lactational performance of ewes, lamb growth, health, body composition, and endocrine status were altered by gestational nutrition in this study (Meyer et al, 2010b;Camacho et al, 2011;C. J.…”
Section: Potential Impacts Of Milk Productionmentioning
confidence: 55%
“…While T 4 is the most predominant thyroid hormone in circulation (Piosik et al, 1997), with concentrations increasing in the lamb before parturition and declining rapidly within the first few days of life (Forhead and Fowden, 2014), T 3 is deemed the most biologically active (Choksi et al, 2003;Rose et al, 2007). There is a strong relationship between both total the free thyroid hormone fractions with circulating levels of T 3 arising from the de-iodination of T 4 by a selenium containing enzyme, type 1 iodothyronine 5'-deiodinase (Barry et al, 1983;Camacho et al, 2012). However, in the current study a lower concentration of free T 3 was observed in lambs born to CaIO 3 ewes.…”
Section: Discussionmentioning
confidence: 99%
“…Although global nutrient restriction and excess (driven by intake changes) and altered supply of major nutrient classes can clearly have effects on offspring outcomes, supply of specific nutrients in the maternal diet can also result in changes in offspring outcomes and have long-term consequences. Research from our laboratories investigating supranutritional selenium supply in maternal diets ( Caton et al, 2007 ; Ward et al, 2008 ; Vonnahme et al, 2010 ; Camacho et al, 2012 ; Meyer et al, 2013 , Yunusova et al, 2013 ; Caton et al, 2014a , 2014b ) has demonstrated changes in lamb birth weight, growth, nutrient digestion, glucose metabolism and insulin sensitivity, visceral fat content, intestinal vascularity, and endocrine profiles in some but not all studies.…”
Section: Maternal Nutrition and Developmental Programmingmentioning
confidence: 99%